THE RIGHT TO INFORMATION AND MISLEADING: A MEANS OF CONCRETING CITIZENSHIP IN BRAZIL ADVERTISING IN THE LABELING OF FOOD PRODUCTS: (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to demonstrate how the practice of misleading advertising in the labeling of food products occurs, in disregard of the consumer's right to information. Advertising is part of the daily life of society and not unlike other branches, it is very present in the foodstuff. Many of these products are misleadingly labeled, aiming to deceive their consumers, through misleading advertising practices, contrary to what guides the principle of good faith and what the consumer's right to information protects. In view of the precariousness of the information provided in the relationship of consumption of food products, especially with regard to the composition, characteristics and quality of the products, making it possible for suppliers to distort such data while the respective buyers are misled. Faced with this scenario, the protective mantle arising from the Federal Constitution and the Consumer Protection Code, sometimes, remains insufficient to preserve consumers. In view of the Government's inertia in producing effective mechanisms to enforce the protection of consumer rights, it is necessary to discuss the Right to Information, which encompasses the duty to inform and the right to be informed, in addition to the necessary imposition of more complex regulations. criteria for advertising on the labeling of food products. Keywords: Right to information. Food labeling. Misleading advertising. Consumer rights.